RETRIEVING DOCUMENT WITH COMPACT GENETIC ALGORITHM(cGA) - Hameed, Sarab; Abdul-Hussain, Maisaa; Ahmed, Zayneb (Iraqi Journal of Science, 2024)
Information retrieval is the task, given a set of documents and a user query, of finding the relevant documents. Information retrieval applications require speed, consistency, accuracy and ease of use in retrieving relevant texts to satisfy user queries. This paper presents an automatic tool to retrieve documents based on Compact Genetic Algorithm (cGA). The similarity between queries and documents is computed with cosine coefficient, dice’s coefficient, and Jaccard coefficient that are used as the fitness functions. Experimental results show that cGA can be successfully applied to information retrieval.